2019
DOI: 10.2174/1874120701913010033
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Segmentation and Classifier Approach Based on HMM for Brain Cancer Detection

Abstract: Introduction: Brain tumors are fatal diseases that are spread worldwide and affect all types of age groups. Due to its direct impact on the central nervous system, if tumor cells prevail at certain locations in the brain, the overall functionality of the body is disturbed and chances of a person approaching death are high. Tumors can be cancerous or non-cancerous but in many cases, the chances of complete recovery are less and as a result death rate has increased all over the world despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Existing work reported in the literature has shown that the classification of brain images is possible via supervised techniques such as ANN, Bayesian networks, k-NN, GMM, HMM, decision tree induction, rule-based classification, PCA and SVM [88,166,182], and via unsupervised techniques such as SOM and FCM. In reality, unsupervised classification, which does not require training data, has not been widely used in CAD systems, due to the specificity of the brain images in which the CAD system should be trained according to the truth field or clinical evidence.…”
Section: Critical Discussion About Classification Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing work reported in the literature has shown that the classification of brain images is possible via supervised techniques such as ANN, Bayesian networks, k-NN, GMM, HMM, decision tree induction, rule-based classification, PCA and SVM [88,166,182], and via unsupervised techniques such as SOM and FCM. In reality, unsupervised classification, which does not require training data, has not been widely used in CAD systems, due to the specificity of the brain images in which the CAD system should be trained according to the truth field or clinical evidence.…”
Section: Critical Discussion About Classification Techniquesmentioning
confidence: 99%
“…It is possible to express a posterior probability of a label field from an observation in hidden Markov models (HMM), thanks to the Bayes theorem. HMMs [84][85][86][87][88] make it possible to model arbitrary characteristics of observations, making it possible to inject knowledge specific to the problem encountered into the model, in order to produce an ever finer resolution of spectral, spatial and temporal data. In the case of HMMs, the types of previous distributions that can be placed on masked states are severely limited; it is not possible to predict the probability of seeing an arbitrary observation.…”
mentioning
confidence: 99%
“…The World Health Organization states that degenerative diseases are the leading cause of death worldwide in the population aged 65 and older, with a higher death toll in developing countries. According to study [13], an estimated 23% of women and 14% of men aged over 65 suffer from degenerative diseases. The global prevalence of hypertension is estimated to be around 15-20%, with a higher incidence in the age group of 55-64 years.…”
Section: A Degenerative Diseasesmentioning
confidence: 99%
“…Hidden Markov Models (HMM) have been proven to perform significantly better than Support Vector Regression (SVR) models when used for brain tumor segmentation. Particular research has focused this topic on how HMM can produce a better Peak Signal-to-Noise Ratio (PSNR) and Mean Squared Error (MSE) [26]. The research applies a HMM to a two-dimensional MRI scan, extracted from the BITE dataset [27].…”
Section: Classifiersmentioning
confidence: 99%